Determining the effectiveness of vitamin C in skin care by atomic force microscope. Issue 9 (17th May 2019) - Dulińska‐Molak, Ida; Pasikowska‐Piwko, Monika; Dębowska, Renata; Święszkowski, Wojciech; Rogiewicz, Katarzyna; Eris, Irena
Abstract: This article presents the results of experiments, which examine cell mechanisms with the goal of confirming the effective action of the active ingredients used in anti‐aging cosmetics. Skin stiffness measurements with the use of an atomic force microscope on two forms of vitamin C (ascorbyl tetraisopalmitate andl ‐ascorbic acid) have been presented. The estimated Young's modulus for three types of cells (a control as well as cells treated with two forms of vitamin C) has shown significant differences in the stiffness of the tested cells which was confirmed in the histological staining experiment. The presented results indicate the dependence between collagen synthesis and the stiffness of cells treated with two forms of vitamin C. Abstract : The study revealed a change in the stiffness of skin cells treated with vitamin C. The pure L‐ascorbic acid (LAA) is more effective than its oil‐soluble ester in anti‐aging effect. The Young's modulus is a good parameters to confirm the effectiveness of cosmetics.